Pengembangan Modul Seni Kreatif dalam Memberikan Layanan Bimbingan Konseling Inovatif - Alfi Rahmi; Nurhasnah Nurhasnah (Islamic Counseling : Jurnal Bimbingan dan Konseling Islam, 2020)
This study aims to develop a creative arts module in counseling so that there are innovations in guidance and counseling services. Visual arts are one of the creative arts in counseling that can help someone relax the burdens they feel in everyday life. Visual Arts in creative counseling can be given to clients who have difficulty verbally expressing their problems. Visual arts can be an alternative for Guidance and Counseling Teachers in schools in carrying out counseling services. This research is a type of development research using the Borg and Gall model. The steps taken are collecting initial information, planning, product development, product validation and testing, product revision, field testing and product end revision. Product trials were carried out on Guidance and Counseling Teachers at the junior high school level in East Agam and in Focus Group Discussion (FGD) activities. The results of the phase I module validation with a value of 15.8 where the module still needs to be revised including discussion of module content, as well as more interesting module design. Then the results of the practicality test with a value of Practical Enough, namely 3.8. The results of the phase II module verification with a value of 16.6 indicate that the module is suitable for use by the Guidance and Counseling Teacher and the results of the practicality test 4.01.